Kapitalisme dalam Industri Media TikTok: Komodifikasi “Keranjang Kuning” terhadap Produksi Konten - Qolbiyah, Syifaul; Firdaus, Salsabil Fadilah; Ulfa, Wildana (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2026)
This study examines how capitalism operates within the TikTok platform through the commodification of content creators, specifically via the yellow cart feature. Using a descriptive qualitative method based on literature review, data were gathered from academic articles, books, and relevant reports. The findings reveal that the yellow cart functions as a direct monetization channel, incentivizing creators to embed affiliate products into their content. This mechanism shifts creators' motivations from self-expression to market-oriented goals. TikTok’s algorithm amplifies such content by increasing the visibility of videos containing affiliate links, thereby reinforcing a rapid cycle of production and consumption driven by profit. This has led to a measurable behavioral shift: creators prioritize promotional content over originality, and audiences are increasingly exposed to embedded commercial messages. The study concludes that TikTok serves as an effective vehicle of digital capitalism, reshaping the creator economy and contributing to content homogenization. The practical implication highlights the need for critical digital literacy to navigate platform-driven economic incentives and algorithmic influence.